CORRELATION OF OVERWEIGHT AND OBESITY WITH HYPERTENSION IN THE PRODUCTIVE AGE GROUP IN PALU CITY - Fransisca Rosaria Octavia; Dyana Sarvasti; Yudita Wulandari (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: Data from the Central Sulawesi Health Office also shows that health services for people with hypertension in Palu City were 25.9% in 2019. In 2017 the prevalence of obesity in Palu City was quite high, with a prevalence of obesity cases of 19.85%. The high incidence of hypertension in Central Sulawesi Province is still not controlled and is closely related to unhealthy lifestyles, overweight, and obesity.Purpose: To find out the nutritional status of overweight and obesity in the productive age group, find out the incidence of hypertension in the productive age group, find out the characteristics of each research respondent, and analyze the correlation between overweight and obesity with the incidence of hypertension in the productive age group.Method: This research is an observational analytic study with a cross-sectional approach. The sampling technique of non-probability sampling is consecutive sampling. The research population is people of productive age (15-64 years). As many as 62 respondents are in the Maesa area, Balaroa, and Petobo shelter areas in Palu City. The variables in this study, namely overweight, obesity and hypertension, are included in the nominal scale. In this study, the correlation test between variables will be carried out with a contingency coefficient test. The correlation between variables is considered significant if the p-value <0.05 is obtained.Result: The correlation between overweight and obesity with hypertension was not statistically significant (p= 0.293). The correlation value of 0.132 indicates a very weak correlation strength and is not clinically significant.Conclusion: There is no correlation between being overweight and obesity with the incidence of hypertension in the productive age group.